Why do people discriminate against Jews? - Fox, Jonathan 1968-; Ṭopor, Lev (New York, NY Oxford University Press, 2021)
Jonathan Fox and Lev Topor provide a new and innovative approach to answering the age-old question of why people discriminate against Jews. They examine anti-Jewish discrimination using a two-pronged approach. First, they combine and integrate ideas and theories from classic studies of anti-Semitism with social science theories on the causes of discrimination. Second, they use previously unavailable data on discrimination against Jews in 76 countries with significant Jewish minority populations to analyse the patterns and causes of discrimination.
Keywords: Antisemitism; Religious Discrimination; Conspiracy Theories; Zionism; Propaganda, Anti-Israeli